Experiences and Challenges with Congenital Hypothyroidism Newborn Screening in Indonesia: A National Cross-Sectional Survey - Aman Bhakti Pulungan; Helena Arnetta Puteri; Muhammad Faizi; Paul Leslie Hofman; Agustini Utari; Jean-Pierre Chanoine (MDPI AG, 2024)
The expansion of newborn screening (NBS) for congenital hypothyroidism (CH) is essential to reducing the number of preventable intellectual disabilities in children. Because of logistical issues, including geographic extremes, distinct cultures, and 4.8 million births annually, Indonesia has struggled to achieve universal NBS coverage. A national cross-sectional electronic survey was conducted to explore challenges in CH NBS. Responses from 423 healthcare professionals and program administrators across 30 provinces in Indonesia were collected. The major challenges reported were refusal from families (39.2%), newborns being discharged <24 h (38.3%), and limited availability of filter paper (35.9%). The respondents considered refusal from families to be due to fear, while others did not understand the necessity of CH NBS. The vast majority of respondents believed that parents do not have sufficient understanding regarding CH NBS (96.5%). Our study found that only 38.5% of respondents had received formal CH NBS training, with pediatric endocrinologists being the only profession in which all respondents had been trained. Concerted efforts are needed to improve the access to and availability of resources, increase the capacity for sample collection and analysis, empower healthcare professionals, and develop educational resources to promote understanding and acceptance of NBS amongst families.